Molecular characterisation of the vitellogenin gene (AlVg) and its expression after Apolygus lucorum had fed on different hosts. Issue 9 (22nd January 2016) - Sun, Yang; Xiao, Liubin; Cao, Guangchun; Zhang, Yongjun; Xiao, Yingfang; Xu, Guangchun; Zhao, Jing; Tan, Yongan; Bai, Lixin
Abstract: BACKGROUND: The polyphagous pest Apolygus lucorum is now the dominant pest of Bacillus thuringiensis ( Bt ) cotton in China. In this study, the transcriptional and translational profiles of AlVg influenced by different hosts were identified, and then the correlations between AlVg gene or AlVg protein expression and key population proliferation parameters of A. lucorum were further clarified. RESULTS: AlVg or AlVg expression can be significantly regulated by different host nutrients ( P < 0.05). AlVg or AlVg expression was significantly higher in A. lucorum reared on Bt and conventional cotton than in A. lucorum reared on garland chrysanthemum and broad bean ( P < 0.05), but there was no significant difference between AlVg or AlVg expression in A. lucorum reared on Bt and conventional cotton ( P > 0.05). In addition, there were significant linear regression correlations between AlVg or AlVg expression and total mortality rate of nymphs, female lifespan, per female fecundity and egg hatching rates ( P < 0.05). CONCLUSION: Our results confirm that AlVg or AlVg is the key parameter affecting female fertility of A. lucorum . AlVg and AlVg expression can be influenced by different host nutrients except for Bt toxin. © 2015 Society of Chemical Industry